Respuesta :
Answer:
Part A: You can solve this by elimination by first multiplying the first equation by -1 and then adding. This will cause the y value to cancel out.
-y = -3x + 5
y = 6x - 8
---------------
0 = 3x - 3
3 = 3x
1 = x
Now since we know that x = 1, we can plug it into either equation to find y.
y = 3x - 5
y = 3(1) - 5
y = 3 - 5
y = -2.
This gives us the ordered pair of (1,-2).
Step-by-step explanation:
Part B: If we graphed these two, they would intersect at (1, -2). This is because when you solve a system using any method, the result is the intersection of the lines. Therefore, you found where they would intersect in Part A.